Left-sided hepatic resection for hepatolithiasis: a longitudinal study of 110 patients - Shah, Omar Javed (Blackwell Publishing Ltd, 2012)
BACKGROUND: Hepatolithiasis affecting the left hepatobiliary system is common in the Asia Pacific region. This aim of this study was to describe an experience with the diagnosis and treatment of patients with isolated left-sided hepatolithiasis. METHODS: One hundred and ten patients with isolated left-sided hepatolithiasis who underwent a left-sided hepatic resection between January 1999 and February 2010 were included for further analysis. The clinical profile, cholangiograms, operative procedures and early and late results were examined. RESULTS: Analysis of magnetic resonance cholangiopancreatography (MRCP) and endoscopic retrograde cholangiopancreatography (ERCP) findings revealed left hepatic ductal anatomical details in 101 patients. Three types of left hepatic ductal variations were observed (type 1 in 90.1%, type 2 in 5.9% and type 3 in 4.0% patients). Eighty-four (76.4%) patients had the presence of strictures in the left hepatic ductal system and in 26 (23.6%) patients no strictures could be seen. Out of 84 patients with strictures, 78 could be classified (type I in 89.7% and type II in 10.3%). Of the 110 patients, 75 (68.2%) underwent a left lateral sectionectomy, 33 (30%) a left hepatectomy and 2 (1.8%) patients were treated with a left hepatectomy combined with a caudate lobe resection. Of the patients who underwent a left hepatectomy 11.4% developed a bile leak. Eight per cent of patients who underwent a left lateral sectionectomy had infective complications. During a median follow-up period of 63 (range 3–134) months, 2 (2.1%) patients were discovered to have residual stones and five (5.2%) others possessed recurrent stones. CONCLUSIONS: This study highlights the impact of the presence or absence of bile duct stricture on the clinical and histological profile of patients as well as their operative and the post-operative behaviour. It is concluded that hepatic resection is an appropriate treatment modality in localized left-sided hepatolithiasis.